2022
DOI: 10.1080/19490976.2022.2125739
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microglial physiology by the microbiota

Abstract: The mammalian gut contains a large, complex community of microorganisms collectively termed the microbiota. It is increasingly appreciated that gut microbes are closely integrated into mammalian physiology, participating in metabolic symbiosis, promoting immune function and signaling to a wide variety of distant cells, including the brain, via circulating metabolites. Recent advances indicate that microglia, the brain’s resident immune cells, are influenced by microbial metabolites at all stages of life, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 141 publications
0
13
0
Order By: Relevance
“…Third, the composition of host microbiota linked to chow and other environmental factors in different animal facilities might contribute to differences in inflammasome responses. Indeed, the intestinal microbiota was shown to modulate immune functions and signaling to a wide variety of distant cells, including microglia ( 66 , 67 ). It is worth mentioning in this regard that our studies were performed in three different animal facilities (VIB-Ghent University in Ghent, Belgium; Janssen Pharmaceutica in Beerse, Belgium; RIKEN Center for Brain Science, Saitama, Japan) with similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the composition of host microbiota linked to chow and other environmental factors in different animal facilities might contribute to differences in inflammasome responses. Indeed, the intestinal microbiota was shown to modulate immune functions and signaling to a wide variety of distant cells, including microglia ( 66 , 67 ). It is worth mentioning in this regard that our studies were performed in three different animal facilities (VIB-Ghent University in Ghent, Belgium; Janssen Pharmaceutica in Beerse, Belgium; RIKEN Center for Brain Science, Saitama, Japan) with similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the gut microbiome plays a crucial role in microglial maturation and activation both in healthy individuals and in patients with CNS disease ( Cook and Prinz, 2022 ; Erny and Prinz, 2020 ). Erny et al (2015) demonstrated that GF mice have global defects in microglia and altered cell proportions, leading to an impaired innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome has been shown to influence both the blood–brain barrier (BBB) and brain function [ 129 , 130 ]. Increased intestinal permeability caused by gut dysbiosis allows for the accumulation of microbiome and metabolites in the central nervous system [ 131 , 132 ]. Glaucoma is a multifactorial neurodegenerative disease characterized by the death of retinal ganglion cells (RGCs).…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%
“…The gut microbiome has been shown to influence both the blood–brain barrier (BBB) and brain function [ 129 , 130 ]. Increased intestinal permeability caused by gut dysbiosis allows microbes and metabolites to accumulate in the central nervous system [ 131 , 132 ]. The author Link [ 32 ], in his work, postulated the existence of a resident brain microbiome, and Deng et al [ 33 ] found evidence of intraocular microbiota and ocular-disease-specific microbial signatures in eyes affected by senile cataracts, age-related macular degeneration, and glaucoma, in which the alteration of the blood–ocular barrier (BOB) seems to be involved.…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%